1995
DOI: 10.12693/aphyspola.87.261
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impact Ionization of Shallow Donors on Luminescence in GaAs

Abstract: Luminescence spectra of n-type molecular beam epitaxial layer and semi-insulating liquid encapsulated Czochralski grown bulk GaAs were measured at liquid helium temperature for zero electric field and for fields which caused impact ionization of shallow donors. Application of the electric field caused a decrease in the luminescence intensity and a broadening of all observed structures. It was found that the electric field changed the luminescence spectrum of the n-type material in a dicherent way than it did i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The experiments were performed on samples of an undoped semi-insulating (SI) GaAs with the EL2 as the dominant deep level. A presence of shallow donors and shallow acceptors as well as deep centres other than the EL2 was confirmed by luminescence [2] and thermally stimulated current [3] measurements. Thus it was shown that the investigated material was a doped compensated semiconductor in which a spatially random distribution of localised charges was a source of fluctuations of the electrostatic potential.…”
Section: Introductionmentioning
confidence: 77%
“…The experiments were performed on samples of an undoped semi-insulating (SI) GaAs with the EL2 as the dominant deep level. A presence of shallow donors and shallow acceptors as well as deep centres other than the EL2 was confirmed by luminescence [2] and thermally stimulated current [3] measurements. Thus it was shown that the investigated material was a doped compensated semiconductor in which a spatially random distribution of localised charges was a source of fluctuations of the electrostatic potential.…”
Section: Introductionmentioning
confidence: 77%